Developing a Sociopreneurship-Based Entrepreneurial Spirit in the Young Generation to Support a Sustainable Economy - Muhammad Syafri (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This community service program aims to develop an entrepreneurial spirit based on sociopreneurship among young generations to support sustainable economic development. The program was conducted through training, mentoring, and practical implementation involving youth communities in Medan. The approach used participatory methods, including workshops on business innovation, social value creation, and sustainable entrepreneurship practices. The results indicate an increase in participants' understanding of sociopreneurship concepts, business creativity, and their ability to identify social problems as business opportunities. Furthermore, participants showed improved motivation and readiness to establish socially-oriented businesses. This program contributes to strengthening youth capacity in building sustainable enterprises that not only generate profits but also create social impact.